Immunological and inflammatory profiles in mild and severe cases of COVID-19 - Jin-Wen Song (Nature Portfolio, 2020)
Immunophenotyping of patients with COVID-19 is ongoing, but much remains to be learned. Here the authors analyze 41 hospitalized patients with COVID-19 and show a higher degree of lymphopenia in various immune cell subsets as well as cytotoxicity and T cell inhibitory marker expression in severe cases compared with mild.